Investigating Factors Influencing Grade 9 and 12 Learner-Performance in Science – Views of School Administrators, Teachers, and Learners: The Case of Eastern Province, Zambia - Mapulanga, Thumah (World Journal of Vocational Education and Training, 2019)
This study investigated the factors that contribute to poor performance in science among grade 9 and 12 learners in the Eastern province of Zambia. The study employed a cross-sectional research design involving 137 participants attending the Zambia Association for Science Education (ZASE) Eastern Provincial Conference held in February 2019 and 74 (24 boys, 50 girls) grade 12 learners. Data were collected using open-ended questions that participants discussed in groups before presenting their findings at the conference. Data were also collected using a document analysis of the Eastern Province Strategic Plan for 2018 - 2021. The data were analysed using thematic qualitative methods and while other data were quantified for further analysis. The findings indicated that factors that influence performance in science fell into six categories namely (a) Administrative (b) Teacher (c) Learner (d) Time allotted to science teaching and learning (e) Assessment and (f) Curricular factors. More specifically, the study revealed that lack of resources such as laboratory apparatus, inadequate preparation by teachers, irregular assessment and a lack of adequate scientific knowledge were among factors that contribute to poor performance in science by learners. The study also revealed that conducting practicals, enhancing assessment, motivating learners and providing teaching and learning materials can improve learner performance in science. Therefore, it is recommended that stakeholders follow-up on the proposed strategies in order to improve learner performance in science. Further, action research needs to be conducted focusing on addressing teacher and learner factors that influence performance in science subjects.